2012
DOI: 10.1177/1352458512446169
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio of multiple sclerosis in the National Swedish MS Register (SMSreg)

Abstract: There is no evidence for an increasing women-to-men ratio with time amongst Swedish multiple sclerosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 25 publications
3
50
3
2
Order By: Relevance
“…For example, a recent analysis of trends in the sex ratio in MS for individuals born between 1930 and 1989 found a marked increase in Northern Europe (not including the UK) (from 2.09 to 3.77), but only a moderate increase in Southern Europe (from 1.46 to 2.31) 16. In contrast, a study in Sweden found a mean female-to-male ratio for MS of 2.62, with no clear trend with year of birth for individuals born between 1931 and 1985 17. A recent review reported a significant increase in the MS prevalence female-to-male sex ratio in the UK between 1949 and 2009—a much longer time period than our study 18.…”
Section: Discussionmentioning
confidence: 85%
“…For example, a recent analysis of trends in the sex ratio in MS for individuals born between 1930 and 1989 found a marked increase in Northern Europe (not including the UK) (from 2.09 to 3.77), but only a moderate increase in Southern Europe (from 1.46 to 2.31) 16. In contrast, a study in Sweden found a mean female-to-male ratio for MS of 2.62, with no clear trend with year of birth for individuals born between 1931 and 1985 17. A recent review reported a significant increase in the MS prevalence female-to-male sex ratio in the UK between 1949 and 2009—a much longer time period than our study 18.…”
Section: Discussionmentioning
confidence: 85%
“…5 A recent study, based on several thousand MS patients, identified through the Swedish MS registry (SMSreg), contradicted this notion. 6 In this study there was no evidence for an increasing F/M ratio either in the prevalence proportion by year of birth (performed between 1931 and 1985) What are the reasons underlying the different results obtained in the first and second analysis? Thanks to the availability of a unique personal identifying number (PIN) which is assigned to everyone at birth or at immigration since 1961 in Sweden, the authors were able to gather information on the same person in several nationwide registries (SMSreg, PAR, Swedish National Population Registry and Cause of Death Registry).…”
mentioning
confidence: 53%
“…It has been difficult to objectively track 25(OH)D concentrations over time, because of high variability in laboratory assays. However, recent studies from Sweden show rising MS incidence [24] over a similar time course as decreasing 25(OH)D levels [25] in blood samples that had been stored and analyzed in a single laboratory at one time point (Figure 4). …”
Section: Ecological Studies Provide the First Links Between Exposumentioning
confidence: 92%